Evaluasi Hasil Belajar Pendidikan Jasmani Olahraga dan Kesehatan Siswa Program Full Day School dan Boarding School (Studi Kasus di SMPIT Insan Kamil Karanganyar)) - Ikhsanudin, Muhammad; Indarto, Pungki (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to describe the effectiveness of student learning outcomes through evaluating the learning outcomes of full day and boarding school program students in PJOK subjects which are divided into male groups and female groups. This research is qualitative research with a case study approach. The subjects of this research were 52 full day program students and 42 boarding school program students. This research uses observation, interview and documentation data collection techniques. The results of the research show that there is a difference in the learning outcomes of students in the full day program and the boarding school program with the average score for the male group in the full day program for knowledge scores and practice scores respectively 90.6 and 88.49 and the average score for the male group in the program boarding school for knowledge scores and practice scores respectively 92 and 88.72 while the average score for the full day program girls group for knowledge scores and practice scores was 90 and 89.3 respectively and the average score for the girls group boarding school program for knowledge scores and practice scores respectively 91 and 89.9. Conclusion, the boarding school program has a better level of effectiveness compared to the full day program as indicated by the average score of boarding school program students which is higher than the score of full day program students. Keywords: Boarding School, Effectiveness Full Day School, Learning Outcomes, PJOK